PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI KEPUASAN KERJA PEGAWAI SEBAGAI VARIABEL INTERVENING (STUDI PADA SUKU DINAS TENAGA KERJA, TRANSMIGRASI, DAN ENERGI KOTA ADMINISTRASI JAKARTA UTARA) - Luthfan Fayi Anzika (2023)
This research is a quantitative study with the aim of knowing the direct and indirect effects of workload and work environment on organizational citizenship behavior through job satisfaction as an intervening variable. The study used a sample of 50 employees at the North Jakarta Administrative City Manpower, Transmigration and Energy Sub-agency using a saturated sampling technique. The analysis technique used in this study is descriptive analysis technique and inferential analysis using the SmartPLS 3.0 application. Testing the hypothesis obtained the results (1) workload has a positive and significant effect on organizational citizenship behavior. (2) the work environment has a positive and significant effect on organizational citizenship behavior. (3) workload has a positive and significant effect on job satisfaction. (4) the work environment has a positive and significant effect on job satisfaction. (5) job satisfaction has a positive and significant effect on organizational citizenship behavior. (6) workload has a positive and significant effect on organizational citizenship behavior through job satisfaction. (7) the work environment has a positive and significant effect on organizational citizenship behavior through job satisfaction.